Análise energética do processo de pirólise lenta da casca de arroz - Resende, Fernando Henrique Rufino [UNESP] (2017)
The rice husk, byproduct with the highest amount in rice production, it is one of the most important agroindustrial residues. Its current disposition cause environmental impacts. One way to use the rice husk is in the pyrolysis process. The literature exhibits many studies about the rice husk pyrolysis, however, there are few studies that perform the energetic analyze of the rice husk slow pyrolysis process. In this work, it was done an energy analysis of the slow pyrolysis process of rice husk, evaluating the effects of temperature in pyrolysis product yields, in the immediate analysis of biochar, in SCP of bio-oil and biochar, and in the energy consumption ratio. The temperatures considered were: 300°C, 400°C and 500°C. The results showed that in all three temperatures the value of ECR (energy consumption ratio) was lower than 1, indicating that the energy contained in the products is greater than the total energy consumption of the rice husk slow pyrolysis process. The best ECR (0.035) was obtained in 300 °C, where it was the biggest biochar fraction (68.40%), the smallest bio-oil fraction (7.22%) and a significant pyrolytic gas fraction (24.38%)